The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1371/journal.pone.0105255
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Infection by Trypanosoma cruzi and Trypanosoma rangeli on the Reproductive Performance of the Vector Rhodnius prolixus

Abstract: The insect Rhodnius prolixus is responsible for the transmission of Trypanosoma cruzi, which is the etiological agent of Chagas disease in areas of Central and South America. Besides this, it can be infected by other trypanosomes such as Trypanosoma rangeli. The effects of these parasites on vectors are poorly understood and are often controversial so here we focussed on possible negative effects of these parasites on the reproductive performance of R. prolixus, specifically comparing infected and uninfected c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 54 publications
5
59
0
1
Order By: Relevance
“…This parasite concentration is similar to that used in several other published studies of T. cruzi infection in triatomines, 9,44,46,50,[54][55][56][57][58][59] and blood meals taken by triatomines at this parasite concentration lead to infective doses that fall within the range of peak parasitemias observed in mice and guinea pigs experimentally infected with T. cruzi. 25,27,[60][61][62][63] Insect infection: insect preparation and feeding.…”
Section: Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…This parasite concentration is similar to that used in several other published studies of T. cruzi infection in triatomines, 9,44,46,50,[54][55][56][57][58][59] and blood meals taken by triatomines at this parasite concentration lead to infective doses that fall within the range of peak parasitemias observed in mice and guinea pigs experimentally infected with T. cruzi. 25,27,[60][61][62][63] Insect infection: insect preparation and feeding.…”
Section: Methodssupporting
confidence: 80%
“…Epimastigote forms of T. cruzi were cultured at 28°C in RPMI-1640 liquid medium (Sigma-Aldrich, St. Louis, MO) supplemented with 10% fetal bovine serum 42,43 and collected in their exponential growth phase for insect infection, as in several similar studies. 9,38,[44][45][46][47][48][49][50][51] To calculate the parasite concentration in culture medium, we gently swished flasks containing the parasites in the medium to facilitate even parasite dispersion. We pipetted the parasites into a 0.5% formalin-phosphate-buffered saline (PBS) solution, and then counted them in a Neubauer cell counter under a compound light microscope.…”
Section: Methodsmentioning
confidence: 99%
“…rangeli is considered to be pathogenic to its invertebrate hosts, being responsible for triatomine death (1,6,41,42). It is known that several aspects of the physiology of the triatomines are altered during infection by T. rangeli, including reduced immune responses, anti-hemostatic activity of the salivary glands, and behavioral changes such as molting delays, changes in the movements of the insects, decreased reproductive performance and increased mortality (29,43,44). However, the mortality rates in our study were much higher than those observed in other studies analyzing T. rangeli experimental infection (2,25).…”
Section: Discussionmentioning
confidence: 99%
“…prolixus , within 3–4 days post-moult, were fed on inactivated rabbit blood (37°C/20min) with culture epimastigotes (parasite) added at a concentration of 1x10 7 parasites/ml. The control was only inactivated blood added with the same amount of culture medium used in the blood with contained parasites [22]. Upon feeding, insects were housed in a temperature-control chamber at 26°C until moulting to the third instar.…”
Section: Methodsmentioning
confidence: 99%